Transcriptomics-based drug repurposing unravels novel therapeutic strategies in AML - TURANLI, BESTE; ARĞA, KAZIM YALÇIN; YILMAZ, BETÜL (My University, 2022)
Acute myeloid leukemia (AML) is a disease of the hematopoietic system in which abnormal cells multiply rapidly, accumulate in the blood and bone marrow, and prevent the production of healthy blood cells. To date, first-line treatment of AML has been based primarily on conventional chemotherapy. Despite progress, the rate of complete remission in AML remains low, especially in older patients, and the relapse rate after complete remission remains high. The combination of clinical and laboratory data has been shown to play an important role in the development of new therapeutic strategies in AML, in addition to features of tumor histopathogenesis and transcriptional regulation. 1 Therefore, we integrated transcriptomics data from relapsed, refractory, and previously untreated AML patients based on their response to therapy using disease-specific signatures with biological and pharmacological data to enable rational identification of the potential of signaling pathways and drugs in AML. Based on the integration of transcriptomics data, we identified eight drug candidates by repurposing and evaluated their potential by in vitro testing in the HL60 and KG -1 cell lines. Six repurposed drugs, including nortriptyline, desipramine, doxepin, estramustine, risedronate, and hydrochlorothiazide, were proposed as potential drug candidates for the treatment of AML. We confirmed possible mechanisms of action of the drugs on cell viability HL -60 and KG -1 by apoptosis assays and Western blotting. Given the beneficial effects of the drugs on the apoptosis pathway, our results are intriguing and suggest that these therapies may prove useful and be potential candidates for the future treatment of AML.